Pollen transport networks reveal highly diverse and temporally stable plant–pollinator interactions in an Appalachian floral community - Barker, Daniel A; Arceo-Gomez, Gerardo (AoB plants, 2021)
Floral visitation alone has been typically used to characterize plant–pollinator interaction networks even though it ignores differences in the quality of floral visits (e.g. transport of pollen) and thus may overestimate the number and functional importance of pollinating interactions. However, how network structural properties differ between floral visitation and pollen transport networks is not well understood. Furthermore, the strength and frequency of plant–pollinator interactions may vary across fine temporal scales (within a single season) further limiting our predictive understanding of the drivers and consequences of plant–pollinator network structure. Thus, evaluating the structure of pollen transport networks and how they change within a flowering season may help increase our predictive understanding of the ecological consequences of plant–pollinator network structure. Here we compare plant–pollinator network structure using floral visitation and pollen transport data and evaluate within-season variation in pollen transport network structure in a diverse plant–pollinator community. Our results show that pollen transport networks provide a more accurate representation of the diversity of plant–pollinator interactions in a community but that floral visitation and pollen transport networks do not differ in overall network structure. Pollen transport network structure was relatively stable throughout the flowering season despite changes in plant and pollinator species composition. Overall, our study highlights the need to improve our understanding of the drivers of plant–pollinator network structure in order to more fully understand the process that govern the assembly of these interactions in nature. Floral visitation has been used to characterize plant–pollinator interactions even though it ignores differences in the quality of floral visits. Insect pollen loads on the other hand can provide more accurate description of the functional consequences of these interactions but this has been little studied. The strength and frequency of plant–pollinator interactions may also vary within a single season further limiting our understanding of the consequences of plant–pollinator interactions. We compared plant–pollinator structure using floral visitation and pollen transport data and evaluate within-season variation in community structure in a diverse plant–pollinator community. Pollen transport data revealed a larger diversity and up to two times as many plant–pollinator interactions. Pollen transport network structure was stable throughout the flowering season despite changes in plant and pollinator species composition. Our study highlights the need to improve our understanding of community-level plant–pollinator interactions and how they are structured in nature.